ESP Pedagogy in Contemporary ELT: Teacher Roles and Methodological Innovations - Verma, Sanjay (Journal of Educational Research and Policies, 2025)
Teaching and Learning is a process having a special purpose. ESP (English for Specific Purposes) is an approach to teaching English that meets the specific needs of learners in academic and workplace settings. This article explores the critical role of ESP teachers as course designers, material providers, researchers, evaluators, and practitioners. It highlights the importance of specialized course design and the challenges faced by ESP teachers in addressing diverse learner requirements.